The Record of Murders and Outrages : Racial Violence and the Fight over Truth at the Dawn of Reconstruction - Blair, William Alan (Book collections on Project MUSE., 2021)
"After the Civil War's end, reports surged of violence by whites against Black men, women, and children. Leaders of the new southern governments and northern Democrats typically denied that the atrocities were happening, or they professed that the levels of violence were nothing more than typical criminal behavior. But as occupying Federal troops grew increasingly aware of and even targeted by violent assaults, in September 1866, Freedmen's Bureau commissioner O.O. Howard requested that assistant commissioners in the states compile reports of 'murders and outrages' to catalog the extent of violence. The Records Relating to Murders and Outrage were assembled to prove that the reports of a peaceful South were wrong. The Freedmen's Bureau papers are one of the most utilized sources for the Reconstruction era, yet the Record of Murders and Outrages has rarely been explored in depth. In this book, William A. Blair takes the full measure of the Bureau's attempt to document and deploy hard information about the reality of the violence that Black communities endured in the wake of Emancipation. A former journalist, Blair is highly attuned to the ways this history reflects on ongoing and contemporary struggles over how trustworthy data is gathered, packaged, shared, and utilized in policymaking and daily life"--